2010
DOI: 10.1080/10447318.2010.516726
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Self-Construals, Motivations, Facebook Use, and User Satisfaction

Abstract: Rare studies have focused on how and why people use social networking sites (SNSs) utilizing individual-level variables such as self-construals and social/nonsocial motivations. This study proposes that the self-construal construct provides a good instrument for measuring the relationship between people's understanding of self as a predictor of social computing (Facebook use) and satisfaction. A survey was conducted with students from a large western U.S. university. Results indicate that interdependent self-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(106 citation statements)
references
References 50 publications
4
98
2
2
Order By: Relevance
“…However the far stretching acceptance of facebook has raised an emerging concern among people regarding its damaging implications on the lives of undergraduates [16]. With over 800 million facebook users, 350 million people can easily access facebook through their cell phones [17]. With the advent of technology, access to these sites is not a problem [18].…”
Section: Discussionmentioning
confidence: 99%
“…However the far stretching acceptance of facebook has raised an emerging concern among people regarding its damaging implications on the lives of undergraduates [16]. With over 800 million facebook users, 350 million people can easily access facebook through their cell phones [17]. With the advent of technology, access to these sites is not a problem [18].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the features of SNSs' own nature explain why Facebook is popular among the youth. Research on SNSs usage have revealed motivations as: social surveillance, recognition, social link, photo sharing, profile editing, creating personal impression, entertainment, creating and developing social network (Köseo lu, 2012;Gülnar, Balc , Çak r, 2010;Joinson, 2008;Kim, Kim, Nam, 2010). Though the motivations and intensity of youth's usage of SNSs are known, it is thought that research related to determining the motivations of generation X are not sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Social motivations were proposed as the cause underlying the popularity of social media (Kim et al, 2010). Besides general usage, socializing was also a salient motivation for news sharing on social media, since forwarding news with a few clicks is an easy way that allowed users to connect and converse with others (Lee & Ma, 2012).…”
Section: Motivation: Uses and Gratification (Uandg) Approachmentioning
confidence: 99%
“…The influences of status-seeking-related motivations were documented in social media studies, e.g., self-expression and Facebook use (Kim et al, 2010); self-development and reputation and Flickr photo sharing (Nov et al, 2009). Self-expression might also be implicit (e.g., in choices of topics and words) when comes to issues that people could not openly discuss (Shao, 2009).…”
Section: Motivation: Uses and Gratification (Uandg) Approachmentioning
confidence: 99%
See 1 more Smart Citation